2017
DOI: 10.3389/fncel.2017.00059
|View full text |Cite
|
Sign up to set email alerts
|

RNF146 Inhibits Excessive Autophagy by Modulating the Wnt-β-Catenin Pathway in Glutamate Excitotoxicity Injury

Abstract: Glutamate induced excitotoxicity is common in diverse neurological disorders. RNF146 as an E3 ubiquitin ligase protects neurons against excitotoxicity via interfering with Poly (ADP-ribose) (PAR) polymer-induced cell death (parthanatos). However, the neuroprotective role of RNF146 has not been fully understood. We aimed to investigate the role of RNF146 in modulating autophagy in HT22 cells under glutamate excitotoxicity injury. Here we found that induction of RNF146 decreased the cellular damage and excitotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…These results indicated that autophagy is beneficial for cells against oxidative stress. Conversely, recent studies found that treatment with 3-MA protected HT-22 cells against glutamate-induced oxidative stress (Yang et al, 2017 ). The inconsistency between our results and previous studies might partially be attributed to different models and time points.…”
Section: Discussionmentioning
confidence: 93%
“…These results indicated that autophagy is beneficial for cells against oxidative stress. Conversely, recent studies found that treatment with 3-MA protected HT-22 cells against glutamate-induced oxidative stress (Yang et al, 2017 ). The inconsistency between our results and previous studies might partially be attributed to different models and time points.…”
Section: Discussionmentioning
confidence: 93%
“…The reaction was stopped by adding 0.4 mol/l of NaOH. Activity of LDH was calculated from absorbance at 440 nm, and the background absorbance from the culture medium that was not used for cell culture was subtracted from all absorbance measurements ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, autophagy was required for the regeneration of astrocytic mitochondrial function during inflammation in the CNS (Motori et al, ). However, excessive autophagy led to the damage of cultured HT22 cells, hippocampal neurons, and striatal neurons after excitotoxicity induced by glutamate, NMDA, or kainic acid (Dong et al, ; Wang et al, ; Yang et al, ). In our study, glutamate exposure inhibited autophagy as confirmed by the change in the LC3‐II/I ratio, p62 expression, and Beclin‐1 levels in cultured astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Excitotoxicity and neuroinflammation are intimately linked to autophagic dysfunction (Ginet et al, 2014;Wang et al, 2017;Yang et al, 2017). In the peripheral nervous system, autophagy prevented inflammation and autophagic inhibition promoted inflammation-induced tissue injury (Kimura, Isaka, & Yoshimori, 2017;Macias-Ceja et al, 2017).…”
Section: Astrocyte Activation Is Accompanied By Lowlevel Autophagymentioning
confidence: 99%